2016
DOI: 10.1155/2016/4687342
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Obstetric Characteristics of Anaemic Pregnant Women Attending Antenatal Clinic in Bolgatanga Regional Hospital

Abstract: The study determined the sociodemographic and obstetric characteristics of pregnant women which contribute to the risk of developing anaemia. A cross-sectional study was conducted among 400 pregnant women attending their first antenatal visit at the Bolgatanga Regional Hospital Antenatal Clinic. Anaemia was significantly associated (p < 0.05) with younger maternal age, parity, gravidity, trimester of pregnancy, and source of drinking water. Multivariate logistic regression identified the following factors with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…Samples in SST were centrifuged at 3000 rpm for 10 min and serum samples were aliquoted into cryotubes and stored at -80 o C until assay. Also, about 2 drops (6 μl) of blood were collected on a slide for the preparation of thick blood film to detect the presence of malaria parasites, according to the protocol described by Ahenkorah et al [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Samples in SST were centrifuged at 3000 rpm for 10 min and serum samples were aliquoted into cryotubes and stored at -80 o C until assay. Also, about 2 drops (6 μl) of blood were collected on a slide for the preparation of thick blood film to detect the presence of malaria parasites, according to the protocol described by Ahenkorah et al [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…These interventions, introducing small-scale, homestead poultry production in concert with promotion of vegetable gardens, field crop production, and/or provision of nutrition education, have shown mixed impacts on anaemia (Galal, Harrison, Abdou, & Zein el Abedin, 1987;Olney, Pedehombga, Ruel, & Dillon, 2015;Olney, Talukder, Iannotti, Ruel, & Quinn, 2009;Osei et al, 2016). The scant observational evidence for the association of livestock rearing with anaemia has similarly shown mixed results with studies reporting higher (Ahenkorah, Nsiah, & Baffoe, 2016;Iannotti et al, 2015) and lower (Flores-Martinez, Zanello, Shankar, & Poole, 2016;Miller, 2010) odds of anaemia associated with livestock rearing. None of these studies has examined the role of coinfection when assessing associations between livestock and anaemia among children, and no epidemiological studies have addressed differential associations among women and children.…”
mentioning
confidence: 99%
“…Although statistically older, several authors [5][6][7][8][9][10] found an age around thirty with a peak between 25 and 34 years, making anemia in pregnancy a pathology of the young adult. However, Alemu [11] in Ethiopia, reports a prevalence of the age group of 40 to 44 years (30%) with a risk three times higher of anemia (OR = 3.43 [1.04-11.28]).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, low educational and socioeconomic levels have been associated with anemia in the literature [8][9][10]15]. Thus, the origin of a rural area increases the risk of anemia by a factor of three [9,10], the absence of employment increases this risk by a factor of five according to Ahenkorah in Ghana [10] and by a factor of 2 according to Taner in Turkey [15]. The latter reports an increase in the risk of anemia twice more in non-school-going pregnant women (ORa = 2.23 [1.35-3.45]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation